Implementation of e-learning in an electronic engineering course - Forero García, Edwin Francisco (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The e-learning methodology bets on a change to the traditional models implemented in educational institutions. In order to test and analyze the results of this new model, it was decided to implement virtual laboratory practices for the electromagnetic conversion course of the undergraduate course in electronic engineering, one of these practices has as title “equivalent circuit of a transformer”, with it and together with the consultation of the levels of satisfaction of students in their learning outcomes, we will build the necessary metrics to evaluate this method.